Impacts of road networks on school enrolment in India - Lee, Cassandra Xiao Hui (Nanyang Technological University, 2023)
In developing countries, the construction of roads improves connectivity, which is a crucial factor in influencing the choice to enrol in school. However, it also allows for better accessibility to more or better low-skill labour opportunities, thereby discouraging further education. Thus, we examine the impact of new road networks on enrolment decisions in India. We discover that having new roads built has a positive association with enrolment rates both directly, and indirectly through the provision of free school meals. We perform heterogeneity analysis and find that the direct positive association holds true across all genders and grade groups, while the indirect positive association only holds true across genders and students in grade 6 to 8.